The Effect of the Crossword Puzzle Learning Model on Students’ Learning Interest in the IPAS Subject for Grade IV at UPT SPF SD Negeri Panaikang II, Makassar City - Pada, Amir; Irfan, Muhammad; Nasiruddin, Nurmalita Sari (International Journal of Elementary School Teacher, 2024)
This research was carried out with the aims: (1) to find out an overview of the application of the Crosswrod Puzzle learning model in Class IV science and science learning at UPT SPF at Panikang II State Elementary School, Makassar City, (2) to find out students' interest in learning in class IV science and science subjects at UPT SPF at State Elementary School. Panaikang II, Makassar City, (3) To determine the effect of applying the Crossword Puzzle model on students' interest in learning in the Class IV Science and Science subject, UPT SPF, Panaikang II State Elementary School, Makassar City. The independent variable in this research is the use of the Crossword Puzzle learning model and the dependent variable is interest. student learning.  The research design used was a Quasi Experimental Design in the form of a Nonequalent Control Group Design. The population in this study was class IV UPT SPF students at Panaikang II State Elementary School, Makassar City. The sample selected in this research was based on purpositive sampling, namely students in class IVA UPT SPF SD Negeri Panaikang II, Makassar City. Data collection techniques in this research are questionnaires, observation sheets, and documentation. The data analysis techniques used are descriptive statistical analysis, descriptive interval analysis, and hypothesis testing using the independent sample t-test. The results of the research show that 1) the Crosswrod Puzzle learning process went well, 2) Students' interest in learning in the experimental class had high criteria after being treated using the Crosswrod Puzzle learning model compared to the control class which did not use the Crosswrod Puzzle learning model in the learning process 3) There is an influence of the Crosswrod Puzzle learning model on the learning interest of class IV UPT SPF SD Negeri Panaikang II students, Makassar City.